Aramid fiber water-dispersible nano-microsphere, coating slurry, diaphragm and preparation method of aramid fiber water-dispersible nano-microsphere

The aramid water-dispersed nano microspheres prepared through interfacial polymerization are mixed with ceramic particles for the coating of lithium battery separators, which solves the problem of insufficient performance of existing separators, improves the circulation performance and high specific capacity of lithium batteries, and achieves safer and more efficient battery performance.

CN119661869AActive Publication Date: 2025-03-21YANTAI TAYHO ADVANCED MATERIALS RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510186201.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-21
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The existing lithium battery separators have insufficient performance in terms of high energy and power density, high operating voltage, wide temperature range, fast charging and discharging speed, and are difficult to meet the safety risks after the energy density of power batteries is increased.

Method used

Aramid water-dispersed nano microspheres with a large specific surface area were prepared by interfacial polymerization, and mixed with ceramic particles to prepare coating slurry, and applied onto the lithium battery separator to improve the thermal stability, electrolyte wetting and porosity of the separator.

Benefits of technology

It significantly improves the circulation performance and high specific capacity of lithium batteries, solves the problems of poor dispersion, low bonding performance and complex preparation process of traditional aqueous aramid nanofiber slurry, and is simple in preparation process and can be used for industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661869A_ABST
    Figure CN119661869A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery diaphragms, in particular to an aramid fiber water-dispersible nano-microsphere, coating slurry, a diaphragm and a preparation method.The preparation method of the aramid fiber water-dispersible nano-microsphere comprises the steps that a diamine monomer, a first dispersing agent and an acid-binding agent are dissolved in deionized water to obtain a water-phase system; dissolving a diformyl chloride monomer in chloroform to obtain an oil phase system; slowly adding the oil-phase system into the water-phase system under the condition of high-speed homogenization to carry out polymerization reaction, and finally carrying out solid-liquid separation, water washing and blending to obtain a water system of the aramid fiber water-dispersible nano-microspheres. According to the preparation method disclosed by the invention, the nanoscale water dispersible microspheres with a relatively large specific surface area are prepared in an interfacial polymerization manner, the particle size of the microspheres is controllable, the thermal stability is good, the microspheres can be stably dispersed in water, and the liquid absorption rate of the diaphragm can be greatly improved; and the coating diaphragm with relatively high diaphragm rupture temperature, relatively low thermal shrinkage and good electrolyte wettability is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to aramid water-dispersible nano-microspheres, coating slurry, diaphragm and preparation method, belonging to the technical field of lithium battery diaphragms. Background Art

[0002] In recent years, with the rapid upgrading of lithium-ion battery technology, lithium-ion batteries have become the mainstream of power batteries used in 3C equipment (communication products, computer products, consumer electronics products), as well as new energy vehicles, large-scale power storage equipment, etc. As an important component of lithium-ion batteries, the diaphragm plays a vital role in the performance of lithium-ion batteries. The diaphragm separates the positive and negative electrode materials and avoids short circuits. Although the diaphragm does not participate in any chemical reaction during the charging and discharging process, it affects the battery's rate, cycle stability and high-temperature safety.

[0003] At present, the mainstream lithium battery separators used in the market are mainly polyolefin microporous membranes, namely dry-stretched PP membranes, wet-stretched PE membranes and three-layer composite membranes of the above two. As lithium-ion battery separators, polyolefin separators have excellent mechanical properties, good electrochemical stability and thermal closure temperature of safety characteristics. However, the inherent disadvantages of the material itself, such as poor thermal dimensional stability, insufficient lyophilic properties and low porosity, are not conducive to the rapid and complete filling of the internal space of the separator by the electrolyte, affecting the ion transmission rate, and restricting the development of lithium ions in terms of high energy and power density, high operating voltage, wide temperature range, fast charging and discharging speed, etc., and the existing polyolefin separators are difficult to meet the above requirements, and with the increase in the energy density of power batteries, it is bound to cause a decrease in the heat dissipation area, resulting in serious safety hazards. Therefore, in order to adapt to the rapid development of lithium-ion batteries, the current research focuses on modifying the separator.

[0004] Surface coating has become one of the important means of modifying polyolefin diaphragms due to its mature, simple and efficient technology. In recent years, there have been more and more studies on coating modification of inorganic ceramics, PVDF and aramid. Although the thermal stability and wettability of coated diaphragms have been greatly improved. However, there are still many problems in these studies. For example, the inorganic coating has poor compatibility with the organic base membrane, the inorganic particles are easy to fall off, the density of inorganic particles is large, and the coating weight increases too much, which is not conducive to the improvement of battery energy density; the temperature resistance of polymers such as PVDF is still not high enough. Among them, aramid has the characteristics of high strength, high modulus, high temperature resistance, chemical corrosion resistance, etc., and it is coated in the battery diaphragm to make it have a higher film rupture temperature, lower thermal shrinkage and good electrolyte wettability, which is unanimously recognized by the domestic and foreign markets.

[0005] At present, aramid coating is mainly oily coating, which uses organic solvents to disperse aramid stock solution to make coating slurry. Oily coating has the advantages of high bonding performance and good comprehensive performance, but its process control is complex, pollution is large, and cost is high. In view of the defects and shortcomings of oily coating, water-based aramid coating slurry came into being, and it has the advantages of low air permeability increment, low pollution, and low price. However, water-based aramid coating slurry has the problems of poor dispersibility, low bonding performance and complex preparation process. At present, water-based coating slurry mainly based on aramid nanofibers is prepared by crushing and grinding large-sized fibers and then dispersing them in water. The prepared aramid nanofibers have the disadvantages of large size, difficult to control and poor dispersibility in water, so that they cannot be well dispersed on the surface of the diaphragm, resulting in uneven diaphragm surface and unstable comprehensive performance, which hinders its application in the field of diaphragm coating. Summary of the invention

[0006] The present invention aims at the deficiencies in the prior art and provides an aramid water-dispersible nano-microsphere, a coating slurry, a diaphragm and a preparation method. A nano-scale water-dispersible microsphere with a large specific surface area is prepared by interfacial polymerization. The water-dispersible microsphere prepared by interfacial polymerization has a controllable particle size, a more uniform particle size, can be stably dispersed in water, and has good thermal stability. The aramid nano-microsphere is mixed with ceramic to prepare the coating slurry, which brings into play the high heat resistance and strong puncture performance of the ceramic. The addition of the aramid nano-microsphere overcomes the problems of poor compatibility between ceramic particles and base membranes and easy shedding of inorganic particles, which can significantly improve the wettability of the electrolyte, the liquid absorption rate of the electrolyte, the ionic conductivity and porosity of the diaphragm, so that the battery has good cycle performance and high specific capacity. In addition, the preparation process is simple and can be widely used in industrialization. The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing aramid water-dispersible nano-microspheres, wherein the method for preparing aramid water-dispersible nano-microspheres is: The diamine monomer, the first dispersant and the acid binding agent are dissolved in deionized water to obtain an aqueous phase system, and the diformyl chloride monomer is dissolved in chloroform to obtain an oil phase system; The oil phase system is slowly added to the water phase system under high-speed homogenization conditions, and a polymerization reaction is carried out under high-speed homogenization conditions to obtain a polymer. Finally, after solid-liquid separation, water washing, and water addition and blending, the water system of the aramid water-dispersible nano-microspheres can be obtained.

[0007] Furthermore, the diamine monomer is at least one of p-phenylenediamine, m-phenylenediamine, and 4,4-diaminodiphenyl ether; The diphthaloyl chloride monomer is at least one of terephthaloyl chloride and isophthaloyl chloride; The acid binding agent is at least one of 2-methylpyridine, calcium hydroxide and sodium carbonate.

[0008] Furthermore, the first dispersant is at least one of polyvinyl pyrrolidone and polyvinyl alcohol.

[0009] Furthermore, the speed of the high-speed homogenization is 2000rpm-10000rpm.

[0010] Further, the molar ratio of the diformyl chloride monomer to the diamine monomer is (0.95-1.05):1; The added mass of the first dispersant is 4%-15% of the total mass of the diamine monomer and the diformyl chloride monomer; The solid content of the polymer is 5-15wt%.

[0011] The present invention also discloses a coating slurry of aramid water-dispersible nano-microspheres, which comprises, by weight: 8-20 parts of aramid water-dispersible nano-microspheres, 20-40 parts of ceramic particles, 2-8 parts of a binder, 0.5-4 parts of a second dispersant, 0.5-2 parts of a wetting agent, and 26-69 parts of deionized water; The aramid water-dispersible nano-microspheres are prepared according to the preparation method of the present invention.

[0012] Furthermore, the particle size of the aramid water-dispersible nano-microspheres is 60-400 nm; The particle size of the ceramic particles is 100-800nm.

[0013] Further, the ceramic particles are at least one of alumina, silica, and boehmite; The binder is at least one of waterborne polyacrylate and modified polyacrylic acid; The second dispersant is at least one of ammonium polyacrylate, sodium polyacrylate, and styrene-maleic anhydride ester; The wetting agent is at least one of polyether-modified siloxane, fatty alcohol polyoxyethylene ether and modified succinic acid.

[0014] The present invention also discloses a method for preparing a coating slurry of aramid water-dispersible nano-microspheres. The method for preparing the coating slurry is as follows: Deionized water, a second dispersant, ceramic particles and a wetting agent are ground and dispersed to obtain a mixed solution, and then a water system of aramid water-dispersible nano-microspheres is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000-1200 rpm to obtain a aramid water-dispersible nano-microsphere coating slurry.

[0015] The invention also discloses a lithium battery coated diaphragm, which is obtained by coating the aramid water-dispersible nano-microsphere coating slurry on both sides of a base film and then shaping and drying the aramid water-dispersible nano-microsphere coating slurry to obtain the lithium battery coated diaphragm.

[0016] The beneficial effects of the present invention are: 1. The present invention uses interfacial polymerization to react under high-speed homogenization conditions to obtain water-dispersible nano-microspheres with controllable particle size, uniform dispersion and good thermal stability. After filtration, washing and preparation, water-dispersible nano-microspheres for coating slurry are directly prepared, which fundamentally solves the shortcomings of traditional water-based aramid nanofiber slurry, such as poor dispersibility, low bonding performance and complex preparation process.

[0017] 2. The aramid water-dispersible nano-microsphere coating slurry prepared by the present invention is an aqueous coating slurry. The aramid nano-water-dispersible microspheres and ceramic particles in the slurry work synergistically, which not only ensures the high heat resistance and strong puncture performance of the coated diaphragm, but also improves its electrolyte wettability, electrolyte absorption rate, ion conductivity and porosity of the diaphragm, and solves the problems of powder loss and low absorption rate of water-based ceramic coating.

[0018] 3. Aramid nano-microspheres are mixed with ceramics to prepare a coating slurry, which brings out the high heat resistance and strong puncture performance of ceramics. The addition of aramid nano-microspheres also overcomes the problems of poor compatibility between ceramic particles and base membranes and easy shedding of inorganic particles. It can significantly improve the wettability of the electrolyte, the liquid absorption rate of the electrolyte, the ionic conductivity and porosity of the diaphragm, thereby giving the battery good cycle performance and high specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of the aramid water-dispersible microspheres prepared in Example 6; Figure 2 This is the thermogravimetric curve of the aramid water-dispersible microspheres prepared in Example 6; Figure 3 This is a scanning electron microscope image of the lithium-electrolyte-coated diaphragm prepared in Example 6; Figure 4 The figure is a comparison of the battery application effects of the lithium-ion coated diaphragms prepared in Example 1 and Example 6 and the commercially available diaphragms; Figure 5 This is a scanning electron microscope image of the aramid water-dispersible microspheres prepared in Comparative Example 5. DETAILED DESCRIPTION

[0020] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0022] A method for preparing aramid water-dispersible nano-microspheres, the method for preparing aramid water-dispersible nano-microspheres comprising: The diamine monomer, the first dispersant and the acid binding agent are dissolved in deionized water to obtain an aqueous phase system, and the diformyl chloride monomer is dissolved in chloroform to obtain an oil phase system; The oil phase system is slowly added to the water phase system under high-speed homogenization conditions, and a polymerization reaction is carried out under high-speed homogenization conditions to obtain a polymer. Finally, after solid-liquid separation, water washing, and water addition and blending, the water system of the aramid water-dispersible nano-microspheres can be obtained.

[0023] Specifically, the diamine monomer is at least one of p-phenylenediamine, m-phenylenediamine, and 4,4-diaminodiphenyl ether; The diphthaloyl chloride monomer is at least one of terephthaloyl chloride and isophthaloyl chloride; The acid binding agent is at least one of 2-methylpyridine, calcium hydroxide and sodium carbonate.

[0024] Specifically, the first dispersant is at least one of polyvinyl pyrrolidone (PVP-K30, purchased from Tianjin Ruijinte Chemical Co., Ltd.) and polyvinyl alcohol (PVA, purchased from Shandong Keyuan Biochemical Co., Ltd.).

[0025] Specifically, the speed of the high-speed homogenization is 2000rpm-10000rpm.

[0026] Specifically, the rate of adding the oil phase system to the water phase system is 20-100 g / min.

[0027] More specifically, the high-speed homogenization speed is R, in rpm; the addition speed of the oil phase system is v, in g / min; then R = r ±100, r = 1340exp(0.02 v ), the high-speed homogenization speed and the oil phase system addition speed satisfy this relationship, which is more conducive to obtaining aramid water-dispersible nano-microspheres with high particle size uniformity.

[0028] Specifically, the molar ratio of the diformyl chloride monomer to the diamine monomer is (0.95-1.05):1; The added mass of the first dispersant is 4%-15% of the total mass of the diamine monomer and the diformyl chloride monomer; The solid content of the polymer is 5-15wt%.

[0029] More specifically, the acid binding agent mainly functions to absorb the acid generated in the system during the polymerization reaction, and its usage is not strictly limited.

[0030] More specifically, the amount of the first dispersant added and the high-speed homogenization speed will affect the particle size of the aramid water-dispersible nano-microspheres. The faster the high-speed homogenization speed, the smaller the particle size of the aramid water-dispersible nano-microspheres. Under the condition of a high-speed homogenization speed of 4000-5000rpm, when the amount of the first dispersant added is 4%-5% of the total mass of the diamine monomer and the diformyl chloride monomer, aramid water-dispersible nano-microspheres with a particle size range of 260-400nm can be obtained; when the amount of the first dispersant added is 8%-10% of the total mass of the diamine monomer and the diformyl chloride monomer, aramid water-dispersible nano-microspheres with a particle size range of 180-240nm can be obtained; when the amount of the first dispersant added is 12%-15% of the total mass of the diamine monomer and the diformyl chloride monomer, aramid water-dispersible nano-microspheres with a particle size range of 60-180nm can be obtained. Aramid water-dispersible nano-microspheres with a suitable particle size range can be selected according to the requirements of the diaphragm coating thickness.

[0031] More specifically, when preparing the aqueous phase system, the mass ratio of the diamine monomer to deionized water is 1:(10-40); when preparing the oil phase system, the mass ratio of the diformyl chloride monomer to chloroform is 1:(2.8-10.5).

[0032] More specifically, the reaction temperature of the polymerization reaction is 5-10°C.

[0033] More specifically, in the embodiment of the present invention, water is added during the preparation process to obtain aramid water-dispersible nano-microspheres with a solid content of 20%.

[0034] A coating slurry for aramid water-dispersible nano-microspheres, comprising, by weight: 8-20 parts of aramid water-dispersible nano-microspheres, 20-40 parts of ceramic particles, 2-8 parts of a binder, 0.5-4 parts of a second dispersant, 0.5-2 parts of a wetting agent, and 26-69 parts of deionized water; The aramid water-dispersible nano-microspheres are prepared according to the preparation method of the present invention.

[0035] More specifically, the mass percentage of each component in the coating slurry to the mass of the coating slurry is: Aramid water-dispersible nanospheres: 8-20wt%; Ceramic particles: 20-40wt%; Binder: 2-8wt%; Dispersant: 0.5-4wt%; Wetting agent: 0.5-2wt%; Deionized water: 26-69wt%.

[0036] The total weight of the above components satisfies 100wt%.

[0037] Specifically, the particle size of the aramid water-dispersible nano-microspheres is 60-400 nm; The particle size of the ceramic particles is 100-800nm.

[0038] Specifically, the ceramic particles are at least one of alumina, silica, and boehmite; The binder is at least one of water-based polyacrylate (model FC-05, purchased from Dongguan Yixing New Material Technology Co., Ltd.) and modified polyacrylic acid (model 8501, purchased from Rongdong New Materials); The second dispersant is at least one of ammonium polyacrylate (model DURAMAX D-3019, purchased from Dow Chemical Co., Ltd.), sodium polyacrylate (model HT-5000, purchased from Nantong Hantai Chemical Co., Ltd.), and styrene-maleic anhydride ester (model SMA, purchased from Luoyang Yefang New Materials Technology Co., Ltd.); The wetting agent is at least one of polyether modified siloxane (model Xinnuo® LD 1710, purchased from Anhui Jiazhi Xinnuo Chemical Co., Ltd.), fatty alcohol polyoxyethylene ether (model AEO-9, purchased from Guangzhou Xiangmei Chemical Technology Co., Ltd.) and modified succinic acid (model OT-75, purchased from Nantong Chenrun Chemical Co., Ltd.).

[0039] A method for preparing a coating slurry of aramid water-dispersible nano-microspheres, the coating slurry being prepared by: Deionized water, a second dispersant, ceramic particles and a wetting agent are ground and dispersed to obtain a mixed solution, and then a water system of aramid water-dispersible nano-microspheres is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000-1200 rpm to obtain a aramid water-dispersible nano-microsphere coating slurry.

[0040] When preparing the mixed liquid, the grinding and dispersing process can not only achieve uniform dispersion, but also adjust the particle size of the ceramic particles. The matching particle sizes of the aramid water-dispersible nano-microspheres and the ceramic particles are more conducive to obtaining a diaphragm with excellent battery application performance, and are more conducive to the ionic conductivity and porosity of the diaphragm.

[0041] More specifically, when preparing the mixed solution, the grinding and dispersing time is 10-60 minutes.

[0042] Preferably, when the particle size of the aramid moisture nano-microspheres used is 60-180 nm, the grinding time is 10-20 min; when the particle size of the aramid moisture nano-microspheres used is 180-240 nm, the grinding time is 20-40 min; when the particle size of the aramid moisture nano-microspheres used is 240-400 nm, the grinding time is 40-60 min.

[0043] A lithium battery coated diaphragm is provided, wherein the aramid water-dispersible nano-microsphere coating slurry is coated on both sides of a base film, and the lithium battery coated diaphragm is obtained after shaping and drying.

[0044] Preferably, the thickness of the lithium-ion coated diaphragm is 6-14 μm.

[0045] More specifically, the base film used in the embodiment of the present invention is a PE base film with a thickness of 7 μm, but this does not constitute a limitation to the technical solution of the present invention.

[0046] Example 1 (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 2.79 g of the first dispersant PVP and 32.72 g of the acid-binding agent 2-methylpyridine were dissolved in 210 g of deionized water to obtain an aqueous phase system. 35.71 g of isophthaloyl chloride monomer was dissolved in 105 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 5000 rpm. The addition rate of the oil phase system was 65 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, aramid water-dispersible nanospheres with a solid content of 20% were obtained.

[0047] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 20wt%; Ceramic particles: 20wt%; Binder: 8wt%; Second dispersant: 2wt%; Wetting agent: 1wt%; Deionized water: 49wt%.

[0048] Preparation of aramid water-dispersible nano-microsphere coating slurry: deionized water, aluminum oxide, modified polyacrylic acid, ammonium polyacrylate and modified succinic acid are added to a stirring tank in sequence according to the composition, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 40 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 51%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0049] Example 2 (1) Preparation of aramid water-dispersible nanospheres: 20 g of p-phenylenediamine monomer, 2.97 g of the first dispersant PVA and 29.26 g of the acid-binding agent pyridine were dissolved in 356 g of deionized water to obtain an aqueous phase system. 39.47 g of terephthaloyl chloride monomer was dissolved in 178 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 2000 rpm. The addition rate of the oil phase system was 20 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, 20% solid content aramid water-dispersible nanospheres were obtained.

[0050] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 8wt%; Ceramic particles: 40wt%; Binder: 6wt%; Second dispersant: 4wt%; Wetting agent: 0.5wt%; Deionized water: 49.5wt%.

[0051] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, boehmite, water-based polyacrylate, styrene-maleic anhydride ester and fatty alcohol polyoxyethylene ether are added to a stirring tank in sequence, and the mixture is obtained by grinding and dispersing, wherein the grinding time is 60 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixture, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 50.5%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0052] Example 3 (1) Preparation of aramid water-dispersible nanospheres: 20 g of 4,4-diaminodiphenyl ether monomer, 2.02 g of the first dispersant PVA and 27.41 g of the acid-binding agent calcium hydroxide were dissolved in 336 g of deionized water to obtain an aqueous phase system. 20.3 g of terephthaloyl chloride monomer was dissolved in 168 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 6000 rpm. The addition rate of the oil phase system was 75 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, 20% solid content aramid water-dispersible nanospheres were obtained.

[0053] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 8wt%; Ceramic particles: 20wt%; Binder: 2wt%; Second dispersant: 0.5wt%; Wetting agent: 0.5wt%; Deionized water: 69wt%.

[0054] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, silicon dioxide, water-based polyacrylate, sodium polyacrylate and polyether-modified siloxane are added to a stirring tank in sequence, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 30 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 31%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0055] Example 4 (1) Preparation of aramid water-dispersible nanospheres: 20 g of p-phenylenediamine monomer, 2.84 g of the first dispersant PVP and 26.86 g of the acid-binding agent calcium hydroxide were dissolved in 758 g of deionized water to obtain an aqueous phase system. 36.84 g of terephthaloyl chloride monomer was dissolved in 379 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 8000 rpm. The addition rate of the oil phase system was 89 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, 20% solid content aramid water-dispersible nanospheres were obtained.

[0056] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 20wt%; Ceramic particles: 40wt%; Binder: 8wt%; Second dispersant: 4wt%; Wetting agent: 2wt%; Deionized water: 26wt%.

[0057] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, aluminum oxide, modified polyacrylic acid, styrene-maleic anhydride ester and polyether-modified siloxane are added to a stirring tank in sequence, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 20 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 74%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0058] Example 5 (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 2.92 g of the first dispersant PVP and 29.26 g of the acid-binding agent pyridine were dissolved in 324 g of deionized water to obtain an aqueous phase system. 38.34 g of isophthaloyl chloride monomer was dissolved in 162 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 7000 rpm. The addition rate of the oil phase system was 82 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, 20% solid content aramid water-dispersible nanospheres were obtained.

[0059] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 15wt%; Ceramic particles: 30wt%; Binder: 6wt%; Second dispersant: 2wt%; Wetting agent: 1wt%; Deionized water: 46wt%.

[0060] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, silicon dioxide, water-based polyacrylate, sodium polyacrylate and modified succinic acid are added to a stirring tank in sequence, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 15 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 54%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0061] Example 6 (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 2.84 g of the first dispersant PVA and 33.75 g of the acid-binding agent 2-methylpyridine were dissolved in 379 g of deionized water to obtain an aqueous phase system. 36.84 g of isophthaloyl chloride monomer was dissolved in 189 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 10,000 rpm. The addition rate of the oil phase system was 100 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After filtering, washing with water and blending three times, 20% solid content aramid water-dispersible nanospheres were obtained.

[0062] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 12wt%; Ceramic particles: 25wt%; Binder: 7wt%; Second dispersant: 2.5wt%; Wetting agent: 1.5wt%; Deionized water: 52wt%.

[0063] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, aluminum oxide, water-based polyacrylate, ammonium polyacrylate and fatty alcohol polyoxyethylene ether are added to a stirring tank in sequence, and the mixture is obtained by grinding and dispersing, wherein the grinding time is 10 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixture, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 48%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0064] Example 7 (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 5.57 g of dispersant PVP and 32.72 g of acid-binding agent 2-methylpyridine were dissolved in 210 g of deionized water to obtain an aqueous phase system. 35.71 g of isophthaloyl chloride monomer was dissolved in 105 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 5000 rpm. The addition rate of the oil phase system was 65 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, aramid water-dispersible nanospheres with a solid content of 20% were obtained.

[0065] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 20wt%; Ceramic particles: 20wt%; Binder: 8wt%; Second dispersant: 2wt%; Wetting agent: 1wt%; Deionized water: 49wt%.

[0066] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, aluminum oxide, modified polyacrylic acid, ammonium polyacrylate and modified succinic acid are added to a stirring tank in sequence, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 30 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 51%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0067] Example 8 (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 8.35 g of dispersant PVP and 32.72 g of acid-binding agent 2-methylpyridine were dissolved in 210 g of deionized water to obtain an aqueous phase system. 35.71 g of isophthaloyl chloride monomer was dissolved in 105 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 5000 rpm. The addition rate of the oil phase system was 65 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, aramid water-dispersible nanospheres with a solid content of 20% were obtained.

[0068] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 20wt%; Ceramic particles: 20wt%; Binder: 8wt%; Second dispersant: 2wt%; Wetting agent: 1wt%; Deionized water: 49wt%.

[0069] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, aluminum oxide, modified polyacrylic acid, ammonium polyacrylate and modified succinic acid are added to a stirring tank in sequence, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 18 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 51%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0070] Example 9 (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 2.79 g of the first dispersant PVP and 32.72 g of the acid-binding agent 2-methylpyridine were dissolved in 210 g of deionized water to obtain an aqueous phase system. 35.71 g of isophthaloyl chloride monomer was dissolved in 105 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 5000 rpm. The addition rate of the oil phase system was 100 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, aramid water-dispersible nanospheres with a solid content of 20% were obtained.

[0071] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 20wt%; Ceramic particles: 20wt%; Binder: 8wt%; Second dispersant: 2wt%; Wetting agent: 1wt%; Deionized water: 49wt%.

[0072] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, aluminum oxide, modified polyacrylic acid, ammonium polyacrylate and modified succinic acid are added to a stirring tank in sequence, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 40 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 51%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0073] Example 10 (1) Preparation of aramid water-dispersible nanospheres: 20 g of 4,4-diaminodiphenyl ether monomer, 2.02 g of the first dispersant PVA and 27.41 g of the acid-binding agent calcium hydroxide were dissolved in 336 g of deionized water to obtain an aqueous phase system. 20.3 g of terephthaloyl chloride monomer was dissolved in 168 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 6000 rpm. The addition rate of the oil phase system was 75 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, 20% solid content aramid water-dispersible nanospheres were obtained.

[0074] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 8wt%; Ceramic particles: 20wt%; Binder: 2wt%; Second dispersant: 0.5wt%; Wetting agent: 0.5wt%; Deionized water: 69wt%.

[0075] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, silicon dioxide, water-based polyacrylate, sodium polyacrylate and polyether-modified siloxane are added to a stirring tank in sequence, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 60 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 31%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0076] Comparative Example 1 The lithium battery coated diaphragm was prepared by the same method as in Example 6, except that no aramid water-dispersible nano-microspheres were added to the coating slurry in Comparative Example 1. The specific process is as follows: (1) The content of each component of the coating slurry is: Ceramic particles: 37wt%; Binder: 7wt%; Second dispersant: 2.5wt%; Wetting agent: 1.5wt%; Deionized water: 52wt%.

[0077] Preparation of aramid water-dispersible nano-microsphere coating slurry: According to the formula composition, deionized water, aluminum oxide, water-based polyacrylate, ammonium polyacrylate and fatty alcohol polyoxyethylene ether were added to a stirring tank in sequence, and the mixture was ground and dispersed to obtain a mixed solution, wherein the grinding time was 10 minutes, and then the mixture was stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a coating slurry with a solid content of 48%; (3) The obtained coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0078] Comparative Example 2 The lithium battery coated diaphragm was prepared by the same method as in Example 6, except that no ceramic particles were added to the coating slurry in Comparative Example 1. The specific process was as follows: (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 2.84 g of the first dispersant PVA and 33.75 g of the acid-binding agent 2-methylpyridine were dissolved in 379 g of deionized water to obtain an aqueous phase system. 36.84 g of isophthaloyl chloride monomer was dissolved in 189 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 10,000 rpm. The addition rate of the oil phase system was 100 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After filtering, washing with water and blending three times, 20% solid content aramid water-dispersible nanospheres were obtained.

[0079] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 37wt%; Binder: 7wt%; Second dispersant: 2.5wt%; Wetting agent: 1.5wt%; Deionized water: 52wt%.

[0080] Preparation of aramid water-dispersible nano-microsphere coating slurry: according to the formula composition, deionized water, water-based polyacrylate, ammonium polyacrylate and fatty alcohol polyoxyethylene ether are added to a stirring tank in sequence, and the mixture is obtained by grinding and dispersing, wherein the grinding time is 10 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixture, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 48%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0081] Comparative Example 3 The lithium-ion coated diaphragm was prepared by the same method as in Example 1, except that the amount of the first dispersant added was reduced (in this comparative example 3, the mass of the first dispersant added was 3% of the total mass of the diamine monomer and the diformyl chloride monomer, which was lower than the amount specified in the present invention). The specific preparation process was as follows: (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 1.67 g of the first dispersant PVP and 32.72 g of the acid-binding agent 2-methylpyridine were dissolved in 210 g of deionized water to obtain an aqueous phase system. 35.71 g of isophthaloyl chloride monomer was dissolved in 105 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 5000 rpm. The addition rate of the oil phase system was 65 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, aramid water-dispersible nanospheres with a solid content of 20% were obtained.

[0082] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 20wt%; Ceramic particles: 20wt%; Binder: 8wt%; Second dispersant: 2wt%; Wetting agent: 1wt%; Deionized water: 49wt%.

[0083] Preparation of aramid water-dispersible nano-microsphere coating slurry: deionized water, aluminum oxide, modified polyacrylic acid, ammonium polyacrylate and modified succinic acid are added to a stirring tank in sequence according to the composition, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 40 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 51%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0084] Comparative Example 4 The lithium-ion coated diaphragm was prepared by the same method as in Example 1, except that the type of the first dispersant was changed (in this comparative example 4, sodium dodecyl sulfate was used as the first dispersant). The specific preparation process is as follows: (1) Preparation of aramid water-dispersible nanospheres: 20 g of m-phenylenediamine monomer, 2.79 g of the first dispersant sodium dodecyl sulfate and 32.72 g of the acid-binding agent 2-methylpyridine were dissolved in 210 g of deionized water to obtain an aqueous phase system. 35.71 g of isophthaloyl chloride monomer was dissolved in 105 g of chloroform to obtain an oil phase system. The oil phase system was slowly added to the aqueous phase system at a high-speed homogenization condition of 5000 rpm. The addition rate of the oil phase system was 65 g / min. The homogenization reaction was carried out at 5°C for 2 h to obtain a white solid powder. After three times of filtration, water washing and blending, aramid water-dispersible nanospheres with a solid content of 20% were obtained.

[0085] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid water-dispersible nanospheres: 20wt%; Ceramic particles: 20wt%; Binder: 8wt%; Second dispersant: 2wt%; Wetting agent: 1wt%; Deionized water: 49wt%.

[0086] Preparation of aramid water-dispersible nano-microsphere coating slurry: deionized water, aluminum oxide, modified polyacrylic acid, ammonium polyacrylate and modified succinic acid are added to a stirring tank in sequence according to the composition, and a mixed solution is obtained by grinding and dispersing, wherein the grinding time is 40 minutes, and then a water system of aramid water-dispersible nano-microspheres with a solid content of 20% is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain a aramid water-dispersible nano-microsphere coating slurry with a solid content of 51%; (3) The obtained aramid water-dispersible nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0087] Comparative Example 5 The lithium-ion coated diaphragm was prepared by the same method as in Example 1, except that: in this comparative example 5, aramid nano-microspheres were prepared by conventional polymerization, and the specific process was as follows: (1) Preparation of aramid nanospheres: 20g of m-phenylenediamine monomer was dissolved in DMAC, and isophthaloyl chloride monomer was added in two batches for polymerization reaction. The total amount of isophthaloyl chloride monomer added was 35.71g. The polymerization reaction temperature was controlled to be 5°C and the stirring speed was 800rpm. After the reaction was completed, neutralization treatment was performed and unreacted reagents were filtered to obtain a polymerization stock solution with a solid content of 16%.

[0088] The polymerization stock solution was mixed with water in a mass ratio of 1:10, and high-speed shearing (5000 rpm) was performed in a precipitation device. After washing, aramid nano-microspheres were obtained, and after blending, aramid nano-microspheres with a solid content of 20% were obtained.

[0089] (2) The contents of the components in the preparation of the aromatic polyamide water-dispersible nano-microsphere coating slurry are as follows: Aramid nanospheres: 20wt%; Ceramic particles: 20wt%; Binder: 8wt%; Second dispersant: 2wt%; Wetting agent: 1wt%; Deionized water: 49wt%.

[0090] Preparation of aramid nano-microsphere coating slurry: deionized water, alumina, modified polyacrylic acid, ammonium polyacrylate and modified succinic acid were added to a stirring tank in sequence according to the composition, and the mixture was ground and dispersed to obtain a mixed solution, wherein the grinding time was 40 minutes, and then a water system with a solid content of aramid nano-microspheres of 20% was added to the mixed solution, and the mixture was stirred and mixed at a speed of 1000 rpm for 30 minutes to obtain an aramid nano-microsphere coating slurry with a solid content of 51%; (3) The obtained aramid nano-microsphere coating slurry is coated on both sides of the base film, and after shaping and drying, a lithium battery coated diaphragm is obtained. The thickness of the lithium battery coated diaphragm is 10 μm.

[0091] The aramid water-dispersible nano-microspheres and lithium-coated diaphragms prepared in the above examples and comparative examples were tested for performance indicators. The specific test results are shown in Table 1 below, where the test methods involved are: The particle size distribution of aramid water-dispersible nanospheres is tested according to standard GB / T 19077-2016; The thermal stability of aramid water-dispersible nanospheres is tested according to standard GB / T 33047.1-2016; The air permeability test of the coated diaphragm is carried out according to the standard GB / T 36363-2018; The heat shrinkage performance of the coated diaphragm is tested at 150°C in accordance with standard GB / T 2027-2004; The liquid absorption rate of the coated diaphragm can be tested by referring to the standard QB / T 2303.11-2008 "Battery pulp layer paper Part 11: Determination of liquid absorption rate".

[0092] Table 1 Performance test data

[0093] It can be seen from the data in the above table that: Example 1-Example 10 The aramid water-dispersible nano-microspheres prepared by the preparation method of the present invention have the advantages of controllable particle size, uniform particle size distribution, and good thermal stability, and can be stably dispersed in water. They are synergistically used with ceramic particles in lithium battery coated diaphragms to prepare water-based aramid coated diaphragms with high film rupture temperature, low thermal shrinkage and good electrolyte wettability, and can solve the problem of powder falling of the coated diaphragm. In addition, the preparation process is simple and can be widely used in industrial production. Figure 1 This is a scanning electron microscope image of the aramid water-dispersible microspheres obtained in Example 6. Figure 1 It can be seen that the aramid water-dispersible microspheres prepared by the preparation method of the present invention have good dispersibility and uniform particle size distribution; Figure 2 The thermogravimetric curve of the aramid water-dispersible microspheres prepared in Example 6 is shown in FIG. Figure 2 It can be seen that the initial decomposition temperature of aramid nanospheres is higher than 430°C, and the microspheres have good thermal stability, which can meet the application requirements of lithium battery coating diaphragms; Figure 3 This is a scanning electron microscope image of the lithium-ion coated diaphragm obtained in Example 6. Figure 3 It can be seen that the aramid water-dispersible nano-microspheres and ceramics are evenly mixed and dispersed on the surface of the base film, and the film surface is flat.

[0094] From the data of Example 1, Example 7, and Example 8, it can be seen that the method for preparing aramid water-dispersible nano-microspheres of the present invention can control the particle size of aramid water-dispersible nano-microspheres by adjusting the amount of the first dispersant added. It is more conducive to actual production applications, provides very clear guidance for the production of nano-microspheres with target particle sizes, and improves production efficiency.

[0095] From the comparison of the data of Example 9 and Example 1, it can be seen that the high-speed homogenization speed and the speed of adding the oil phase system in Example 1 cooperate with each other, which is more conducive to obtaining aramid water-dispersible nano-microspheres with higher particle size uniformity.

[0096] From the comparison of the data of Example 10 and Example 3, it can be seen that when the grinding time and the particle size of the aramid water-dispersed nano-microspheres match each other, it is more conducive to obtaining a lithium battery coated diaphragm with excellent performance.

[0097] From the comparison of the data of Comparative Examples 1 and 2 and Example 6, it can be seen that in the coating slurry, the aramid water-dispersible nano-microspheres and ceramic particles cooperate to prepare a lithium-ion coated diaphragm with better performance. If the aramid water-dispersible nano-microspheres are not added, it is found in the experiment that the diaphragm is prone to powdering, and the liquid absorption rate is reduced, thereby affecting the electrolyte wettability of the diaphragm. If the ceramic particles are not added, the thermal shrinkage of the diaphragm is reduced, affecting the high temperature resistance of the diaphragm.

[0098] From the comparison of the data of Comparative Example 3 and Example 1, it can be seen that if the amount of the first dispersant added is reduced, the emulsification is made uniform, which leads to an increase in the particle size of the water-dispersible microspheres and an uneven distribution.

[0099] From the data comparison between Comparative Example 4 and Example 1, it can be seen that if sodium dodecyl sulfate is used as the first dispersant, a stable emulsion structure cannot be formed, resulting in uneven particle size distribution. Therefore, the use of the first dispersant defined in the present invention is more conducive to obtaining aramid water-dispersed nano-microspheres with uniform particle size distribution through interfacial polymerization, and ultimately obtaining a lithium battery coated diaphragm with excellent performance.

[0100] From the comparison of the data of comparative example 5 and example 1, it can be seen that the present invention is more conducive to preparing a kind of aramid nano water-dispersible microsphere with a large specific surface area by interfacial polymerization, and the microsphere particle size is controllable, the thermal stability is good, and it can be stably dispersed in water, which is more conducive to application in lithium battery diaphragms, and can greatly improve the liquid absorption rate of the diaphragm. In addition, the preparation process is simple, the raw materials are simple, and it can be widely used in industrialization. Figure 1 and Figure 5 It can also be clearly seen from the comparison that the aramid nano water-dispersible microspheres obtained by the preparation method of the present invention are more uniform.

[0101] In addition, the lithium battery coated diaphragms prepared in Example 1 and Example 6 and two commonly used lithium battery diaphragms on the market were assembled into lithium batteries using the same method, and the battery performance tests were carried out.

[0102] Battery performance test results are as follows Figure 4 As shown, from Figure 4 From the battery performance test comparison of two commonly used lithium battery separators on the market and the lithium battery coated separators prepared in Example 1 and Example 6, it can be seen that when the separators of Example 1 and Example 6 prepared by the preparation method of the present invention are applied to the battery, the rate performance, high and low temperature rate and cycle performance of the battery are improved.

[0103] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0104] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing aramid water-dispersible nanospheres, characterized in that: The preparation method of the aramid water-dispersible nano-microspheres is as follows: The diamine monomer, the first dispersant and the acid binding agent are dissolved in deionized water to obtain an aqueous phase system, and the diformyl chloride monomer is dissolved in chloroform to obtain an oil phase system; The oil phase system is slowly added to the water phase system under high-speed homogenization conditions, and a polymerization reaction is carried out under high-speed homogenization conditions to obtain a polymer. Finally, after solid-liquid separation, water washing and blending, the water system of the aramid water-dispersible nano-microspheres can be obtained.

2. The method for preparing aramid water-dispersible nanospheres according to claim 1, characterized in that: The diamine monomer is at least one of p-phenylenediamine, m-phenylenediamine and 4,4-diaminodiphenyl ether; The diphthaloyl chloride monomer is at least one of terephthaloyl chloride and isophthaloyl chloride; The acid binding agent is at least one of 2-methylpyridine, calcium hydroxide and sodium carbonate.

3. The method for preparing aramid water-dispersible nanospheres according to claim 1, characterized in that: The first dispersant is at least one of polyvinyl pyrrolidone and polyvinyl alcohol.

4. The method for preparing aramid water-dispersible nanospheres according to claim 1, characterized in that: The speed of the high-speed homogenization is 2000rpm-10000rpm.

5. The method for preparing aramid water-dispersible nanospheres according to claim 1, characterized in that: The molar ratio of the diformyl chloride monomer to the diamine monomer is (0.95-1.05):1; The added mass of the first dispersant is 4%-15% of the total mass of the diamine monomer and the diformyl chloride monomer; The solid content of the polymer is 5-15wt%.

6. A slurry for coating aramid water-dispersible nano-microspheres, characterized in that: The coating slurry comprises, by weight: 8-20 parts of aramid water-dispersible nano-microspheres, 20-40 parts of ceramic particles, 2-8 parts of a binder, 0.5-4 parts of a second dispersant, 0.5-2 parts of a wetting agent, and 26-69 parts of deionized water; The aramid water-dispersible nanospheres are prepared according to the preparation method described in any one of claims 1-5.

7. The aramid water-dispersible nano-microsphere coating slurry according to claim 6, characterized in that: The particle size of the aramid water-dispersible nano-microspheres is 60-400 nm; The particle size of the ceramic particles is 100-800nm.

8. The aramid water-dispersible nano-microsphere coating slurry according to claim 6, characterized in that: The ceramic particles are at least one of alumina, silica, and boehmite; The binder is at least one of waterborne polyacrylate and modified polyacrylic acid; The second dispersant is at least one of ammonium polyacrylate, sodium polyacrylate, and styrene-maleic anhydride ester; The wetting agent is at least one of polyether-modified siloxane, fatty alcohol polyoxyethylene ether and modified succinic acid.

9. A method for preparing the aramid water-dispersible nano-microsphere coating slurry according to any one of claims 6 to 8, characterized in that: The preparation method of the coating slurry is: Deionized water, a second dispersant, ceramic particles and a wetting agent are ground and dispersed to obtain a mixed solution, and then a water system of aramid water-dispersible nano-microspheres is added to the mixed solution, and the mixture is stirred and mixed at a speed of 1000-1200 rpm to obtain a aramid water-dispersible nano-microsphere coating slurry.

10. A lithium battery coated diaphragm, characterized in that: The aramid water-dispersible nano-microsphere coating slurry described in any one of claims 6 to 8 is coated on both sides of the base film, and the lithium battery coated diaphragm is obtained after shaping and drying.

Citation Information

Patent Citations

  • Membrane coating liquid and water-based nano-para-aramid coated membrane

    CN109546056A

  • Inorganic nanoparticle-modified aramid fiber paste and aramid-coated lithium battery composite diagram

    CN110048063A

  • Aramid fiber adhesive as well as preparation method and application thereof

    CN110256667A

  • Water-soluble aromatic polyamide, preparation method and battery diaphragm thereof

    CN118546356A

  • Modified aramid diaphragm coating slurry, battery diaphragm and preparation method of modified aramid diaphragm coating slurry

    CN119176937A